Mitochondrial DNA data analysis strategies that inform MPS-based forensic casework implementation. Issue 1 (December 2019) - Holt, Cydne; Walichiewicz, Paulina; Eagles, Justin; Daulo, Anthony; Didier, Meghan; Edwards, Chris; Fleming, Keenan; Han, Yonmee; Hill, Timothy; Li, Sanja; Rensfield, Anthony; Sa, Daniel; et al.
Abstract: Massively parallel sequencing (MPS) of human mitochondrial control region or whole genome is now faster, easier and more informative than was possible with Sanger sequencing and capillary electrophoresis. This study focuses on the aspects of mtDNA data that are important to consider when implementing MPS-based mtDNA typing into casework operations. This includes evaluation of data from the ForenSeq mtDNA typing system that indicate how interpretation concepts integral to Sanger sequencing of mtDNA apply directly to MPS-based mtDNA typing. In addition, there are new interpretation considerations that may be helpful when determining standard operating procedures and casework interpretation guidelines. Sequencing data are presented that may assist with SOP determination relative to sensitivity assessments that may help inform interpretation criteria, including thresholds, relative to input DNA template concentration ranges, number of pooled samples for MiSeq FGx sequencing runs and downstream bioinformatic demultiplexing. Given the quantitative nature of digital MPS data, these limit of detection studies may also assist when laboratories wish to set criteria for heteroplasmy detection (within an individual) or for mixed DNA sample interpretation. Assessment of variables will be provided across sample types such as hairs and PCR/sequencing inhibition when typing skeletal and dental remains to assist with fundamental understanding of ForenSeq mtDNA typing system limitations as well as metrics that may assist when making data quality determinations.